Correlation between overactive bladder symptom score and neuropsychological parameters in Alzheimer’s disease patients with lower urinary tract symptom - Jung,Ha Bum (2017)
ABSTRACT Purpose To examine an association between the overactive bladder symptom score (OABSS) and neuropsychological parameters. Moreover, we investigate the factors that affect each item in the questionnaire. Materials and Methods A total of 376 patients (males: 184; females: 192) with probable Alzheimer’s disease (AD) were recruited. Cognitive testing was conducted using the Mini Mental Status Examination (MMSE), Clinical Dementia Rating (CDR) scale, Global Deterioration Scale (GDS), and Barthel Activities of Daily Living (ADL). Lower urinary tract symptom (LUTS) was assessed using OABSS and voiding diary. Results The prevalence of overactive bladder (OAB) (defined as OABSS ≥3 with an urgency score of ≥2) in patients with AD was 72.6%. Among the OAB subjects, the most common severity of symptom was moderate (72.6%), followed by mild (21.2%), and severe (5.8%). It was found that OABSS had a very high correlation with aging (r=0.75; p<0.001). When compared with neuropsychological parameters, it was found that OABSS was highly correlated with the CDR scores (r=0.446; p<0.001). However, no significant correlation was found between the changes in OABSS scores and those in other neuropsychological parameters. Based on the individual symptom scores, urgency incontinence was highly correlated with the CDR scores (r=0.43; p<0.001). Conclusions OABSS is a useful tool in assessing AD patients with LUTS. There was a consistent positive association between OABSS severity, including urgency incontinence, and CDR scores.